THE METHODOLOGICAL PROBLEMS OF THE STUDY GLOBALIZATION PROCESS (American Journal of Interdisciplinary Research and Development, 2022)
This article discusses the issues of studying the methodology of globalization, its emergence and development, features and contradictory nature of globalization. The ratio of national and global, as well as features of accession to the globalization of Uzbekistan.